Characterization of organic friction modifiers using lateral force microscopy and Eyring activation energy model. (February 2023) - Hou, Jinchi; Tsukamoto, Masaki; Zhang, Hedong; Fukuzawa, Kenji; Itoh, Shintaro; Azuma, Naoki
Abstract: High-performance organic friction modifiers (OFMs) added to lubricating oils are crucial for reducing friction and wear under boundary lubrication. To guide the development of higher-performance OFMs, the boundary lubrication characteristics and working mechanisms of existing OFMs should be elucidated. In this study, the nanoscale frictional properties of conventional and recently developed TEMPO-based OFMs were measured using lateral force microscopy and interpreted using the Eyring activation energy model. We found that the parameters in this model provided insights into the characteristics of OFMs during loaded sliding, including the load-carrying capacity, adsorption speed, and shear-motion location. Therefore, analysis using the Eyring activation energy model effectively complements the LFM measurements and provides a new perspective for evaluating the boundary lubrication characteristics of OFMs beneficial for the development of high-performance OFMs. Highlights: Eyring activation energy model was used to interpret the friction properties of organic friction modifiers (OFMs). This model provides insights into the load-carrying capacity, adsorption speed, and shear-motion location of OFMs. This model explains the superiority of our TEMPO-based OFMs over the conventional ones.